2022
DOI: 10.5799/jmid.1085903
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Virus Transmission from SARS-CoV-2-positive Mothers to Neonates: A Tertiary Care Hospital Experience

Abstract: Objectives:The coronavirus disease 2019 (COVID-19) outbreak is evolving rapidly worldwide. However, little is known about the association between pregnant women with COVID-19 and its transmission to neonates. This investigation aimed to see if COVID-19 infection could be transmitted vertically into the uterus. Methods:We conducted a prospective observational study. 48 COVID-19 infected mothers were enrolled during their third trimester. A qRT-PCR assay of the nasal and oropharyngeal swab samples was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Similarly, there is previous evidence reported that vertical transmission of COVID-19 from mother to child is relatively rare [ 3 , 5 , 8 , 11 , 12 ], although transmission may occur during pregnancy, postpartum, childbirth, and close contact with infected mothers [ 12 ]. In a report, no SARS-CoV-2 virus was detected in the breastmilk of 110 pregnant women during the infection, indicating and discovered that breast milk poses no danger of viral transmission via breastmilk into the newborn [ 11 , 13 ]. There is some controversy exists regarding the presence of SARS-CoV-2 in the amniotic fluid; we reported negativity of amniotic fluid from 396 mothers, and several other studies are also reported in support of our findings.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, there is previous evidence reported that vertical transmission of COVID-19 from mother to child is relatively rare [ 3 , 5 , 8 , 11 , 12 ], although transmission may occur during pregnancy, postpartum, childbirth, and close contact with infected mothers [ 12 ]. In a report, no SARS-CoV-2 virus was detected in the breastmilk of 110 pregnant women during the infection, indicating and discovered that breast milk poses no danger of viral transmission via breastmilk into the newborn [ 11 , 13 ]. There is some controversy exists regarding the presence of SARS-CoV-2 in the amniotic fluid; we reported negativity of amniotic fluid from 396 mothers, and several other studies are also reported in support of our findings.…”
Section: Discussionmentioning
confidence: 69%
“…No evidence of vertical transmission of SARS-CoV-2 was reported in our research findings, as all the other biological samples of mothers such as amniotic fluid, breast milk, cord blood, and placental tissues collected during the pregnancies were tested negative for the presence of SARS-CoV-2. Similarly, there is previous evidence reported that vertical transmission of COVID-19 from mother to child is relatively rare [3,5,8,11,12], although transmission may occur during pregnancy, postpartum, childbirth, and close contact with infected mothers [12]. In a report, no SARS-CoV-2 virus was detected in the breastmilk of 110 pregnant women during the infection, indicating and discovered that breast milk poses no danger of viral transmission via breastmilk into the newborn [11,13].…”
Section: Discussionmentioning
confidence: 70%
“…f) Biomedical research: AMPs are valuable tools in biomedical research for studying host-pathogen interactions, antimicrobial mechanisms, and developing new therapeutic strategies against infectious diseases. [16][17][18] They can also be used as molecular probes for detecting and targeting specific microbial pathogens.…”
Section: Applications Of Ampsmentioning
confidence: 99%
“…There are several mechanisms behind antimicrobial resistance 8,9 for instance, A barrier to some types of chemicals is provided by the LPS (lipopolysaccharide) layer in gram negative bacteria. Because of this, certain bacteria have inbuilt resistance to specific classes of powerful antimicrobial medicines.…”
Section: Mechanism Behind Antibiotic Resistancementioning
confidence: 99%